Investigating DNA methylation patterns in hair samples of patients with COVID-19-related acute telogen effluvium - Jubair, Ali Hilal; Hashim, Hayder Obayes; Makki Al-Hindy, Hayder Abdul-Amir; Baloh, Yasir Hameed (Pharmakeftiki, 2025)
This study has investigated the association between acute telogen effluvium and global DNA methylation in female patients recovering from coronavirus disease 2019 (COVID-19). In a cross-sectional case-control design, 100 participants were enrolled: 50 women presenting with post-COVID-19 hair loss and 50 age-matched healthy controls. Samples were obtained from patients attending consultant physician clinics at the Hilla Teaching Hospital and the Al-Imam Al-Sadeq Teaching Hospital between November 2022 and May 2023. Hair specimens were collected, DNA was extracted, and global methylation levels were quantified using liquid chromatography–mass spectrometry. A correlation was observed between age and the likelihood of hair loss; however, no statistically significant differences in DNA methylation levels were detected between the study groups. These findings suggest that while age may influence susceptibility to post-COVID-19 telogen effluvium, global DNA methylation does not appear to play a major role. Further research is warranted in order to elucidate the contribution of epigenetic mechanisms in post-viral hair loss syndromes.